Prevalence and associated factors of scabies among schoolchildren in Dabat district, northwest Ethiopia, 2018 - Henok Dagne; Awrajaw Dessie; Bikes Destaw; Walelegn Worku Yallew; Zemichael Gizaw (Komiyama Printing Co. Ltd, 2019)
Abstract Background Scabies is a skin infestation caused by the mite Sarcoptes scabiei that causes a pruritic skin eruption. In Ethiopia, the disease is common especially during natural or manmade disasters such as flooding, drought, civil war and conflict, poor water supply and sanitation, and overcrowding living condition. Though scabies is becoming a major public health problem, especially in low resource settings, there has been no study that reported the prevalence of scabies in the study area. The aim of this study, therefore, was to assess the prevalence of scabies and associated factors among students in primary schools in Dabat district, northwest Ethiopia. Method An institutional-based cross-sectional study was employed to determine the prevalence of scabies and associated factors among schoolchildren in Dabat district. A total of 494 students selected by a multi-stage sampling technique were included in this study. Scabies was diagnosed by medical practitioners based on lesions observed on body surfaces after a physical examination. Bivariable and multivariable binary logistic regression analyses were performed using SPSS version 20. Significance level was obtained at p value < 0.05. Result The prevalence of scabies was 9.3% (46/494) with 95% CI (5.66%, 12.94%). Among schoolchildren who were infested by scabies, 65.22% (30/46) had a mild, 28.26% (13/46) had moderate, and 6.52% (3/46) had severe lesions. Studying at a rural school (AOR = 2.99, 95% CI 1.33, 6.71), had illiterate father (AOR = 5.11, 95% CI 2.25, 11.58), being grade level 1-4 (AOR = 3.91, 95% CI 1.69, 9.05), rarely taking a bath (AOR = 3.54, 95% CI 1.36, 9.25), contact with a person with itching symptom (AOR = 2.66, 95% CI 1. 21, 5.83), a family member with itchy symptoms (AOR = 4.76, 95% CI 2.20, 10.28), not living with both parents (AOR = 2.49, 95% CI 1.02, 6.06), and using water only for hand washing (AOR = 4.38, 95% CI 1.78, 10.76) were factors associated with scabies infestation among schoolchildren. Conclusion The prevalence of human scabies among schoolchildren in Dabat district northwest Ethiopia was high. The school localization, first cycle level of education, paternal educational status, frequency of taking a bath, and contact with a person having itchy lesions, presence of a family member with itchy lesion, and type of frequently used hand washing material were the factors significantly impacting the occurrence of scabies. Special attention should be given to students at first cycle education as they are at the highest risk of infestation.